2018
DOI: 10.1038/s41389-018-0055-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of immune suppression for transplantation on inflammatory colorectal cancer progression

Abstract: BackgroundUlcerative colitis patients and transplant recipients are at risk for colorectal cancer. Here, we show that immunosuppressive regimens for kidney transplants are associated with the progression of ulcerative colitis-related carcinogenesis.MethodsWe describe the case of a patient diagnosed with colorectal cancer in ulcerative colitis while on immunosuppressive therapy for a kidney transplant. The immunological microenvironment of the cancer and its mutational status were analyzed, and a mouse colon ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, progression from adenoma to carcinoma may be hastened in the context of immunosuppression (as in the case of kidney transplantation) and persistent inflammation associated with uremia. 4 Performing work-up colonoscopies in all participants regardless of the index test results may mitigate the issue of differential verification bias, but it would be unethical to conduct potentially harmful and unnecessary investigations in individuals who are at risk of serious complications. Nevertheless, to overcome this limitation, performance characteristics of FIT to detect colorectal cancer, a more robust indicator, have been reported separately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, progression from adenoma to carcinoma may be hastened in the context of immunosuppression (as in the case of kidney transplantation) and persistent inflammation associated with uremia. 4 Performing work-up colonoscopies in all participants regardless of the index test results may mitigate the issue of differential verification bias, but it would be unethical to conduct potentially harmful and unnecessary investigations in individuals who are at risk of serious complications. Nevertheless, to overcome this limitation, performance characteristics of FIT to detect colorectal cancer, a more robust indicator, have been reported separately.…”
Section: Discussionmentioning
confidence: 99%
“…1 Sydney School of Public Health, Faculty of Medicine and Health, 19 School of Mathematics and Statistics, and 17 Charles Perkins Centre, The University of Sydney, Sydney, Australia; 2 Centre for Transplant and Renal Research, and 4 Department of Gastroenterology, Westmead Hospital, Westmead, New South Wales, Australia; 5 Gastroenterology Department, Hospital Clinic of Barcelona, University of Barcelona, Barcelona, Spain; 8 Department of Renal Medicine, Gosford Hospital, Gosford, Australia; 10 Department of Renal Medicine, Sir Charles Gairdner Hospital, Perth, Australia; 11 Faculty of Medicine, University of Toronto, Ontario, Canada; 12 Department of Nephrology and Kidney Transplantation, Clinical and Provincial Hospital of Barcelona, Barcelona, Spain; 13 Department of Nephrology and Kidney Transplantation, Christchurch Hospital, Christchurch, New Zealand; 15 Department of Renal Medicine, Concord Repatriation General Hospital, Concord, Australia; 16 Department of Renal Medicine, Royal Prince Alfred Hospital, Camperdown, New South Wales, Australia; 18…”
Section: Affiliationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Angriman et al demonstrated that a reduced Treg subpopulation in mice receiving TAC, cyclosporine, and mTOR inhibitors correlated with the reduced pro-tumorigenic effect of these cells [34]. High expression of IL-2Rβ and IL-2Rγ was detected in NK cells, monocytes, macrophages, and resting CD4+ and resting CD8+ T cells.…”
Section: Tacrolimus After Ltmentioning
confidence: 99%